Plan de marketing para el posicionamiento del establecimiento turístico “cervecería artesanal Blaze Gastropub – Wings beer and burger” en el cantón Guaranda provincia Bolívar año 2023 - Vásconez Klinger, Analía (2024)
The research focused on developing a marketing plan to position the Blaze Craft Brewery Gastropub - Wings, Beer And Burger, located in Ciudadela 7 Colinas, Camilo Montenegro Street, in Bolívar Province. The methodology involved a mixed approach, employing both qualitative and quantitative methods. The qualitative method provided detailed insights from customers regarding food, service, restaurant experience, and expectations, while the quantitative method collected numerical data through surveys to assess customer satisfaction. A SWOT analysis was conducted to evaluate the restaurant's environment, identifying key areas that needed attention and development. The proposed strategies spanned various categories, including marketing and positioning, content creation and dissemination, experiential marketing, and innovation. In terms of marketing and positioning, the proposal included the creation of new social media channels for increased promotion, an attractive promotional message, and modern logos and slogans. Experiential marketing focused on introducing new offers and promotions, such as Saturday 2-for-1 deals and a free beer for every $10 spent, continually seeking ways to enhance the customer experience. Innovation involved the creation of a QR code for the menu and aesthetic modernization. In summary, the comprehensive plan addressed key aspects to enhance the presence and experience of Blaze Brewery, combining marketing, positioning, customer experience, and innovation strategies in pursuit of sustainable growth in the Bolívar Province market.